Inequality measures based on election data 1871 and 1892 for Swedish municipalities - Moricz, Sara (Lund University, 2019)
The data contains inequality measures at the municipality-level for 1892 and 1871, as estimated in the PhD thesis "Institutions, Inequality and Societal Transformations" by Sara Moricz. The data also contains the source publications:
1) tabel 1 from “Bidrag till Sverige official statistik R) Valstatistik. XI. Statistiska Centralbyråns underdåniga berättelse rörande kommunala rösträtten år 1892” (biSOS R 1892)
2) tabel 1 from “Bidrag till Sverige official statistik R) Valstatistik. II. Statistiska Centralbyråns underdåniga berättelse rörande kommunala rösträtten år 1871” (biSOS R 1871)

---------------------------------------------
moricz_inequality_agriculture.csv
---------------------------------------------

A UTF-8 encoded .csv-file. Each row is a municipality of the agricultural sample (2222 in total). Each column is a variable.

R71muncipality_id: a unique identifier for the municipalities in the R1871 publication (the municipality name can be obtained from the source data)
R92muncipality_id: a unique identifier for the municipalities in the R1892 publication (the municipality name can be obtained from the source data)
agriTop1_1871: an ordinal measure (ranking) of the top 1 income share in the agricultural sector for 1871
agriTop1_1892: an ordinal measure (ranking) of the top 1 income share in the agricultural sector for 1892
highestFarm_1871: a cardinal measure of the top 1 person share in the agricultural sector for 1871
highestFarm_1871: a cardinal measure of the top 1 person share in the agricultural sector for 1892


---------------------------------------------
moricz_inequality_industry.csv
---------------------------------------------

A UTF-8 encoded .csv-file. Each row is a municipality of the industrial sample (1328 in total). Each column is a variable.

R71muncipality_id: see above description
R92muncipality_id: see above description
indTop1_1871: an ordinal measure (ranking) of the top 1 income share in the industrial sector for 1871
indTop1_1892: an ordinal measure (ranking) of the top 1 income share in the industrial sector for 1892

---------------------------------------------
moricz_R1892_source_data.csv
---------------------------------------------
A UTF-8 encoded .csv-file with the source data. The variables are described in the adherent codebook moricz_R1892_source_data_codebook.csv.

Contains table 1 from “Bidrag till Sverige official statistik R) Valstatistik. XI. Statistiska Centralbyråns underdåniga berättelse rörande kommunala rösträtten år 1892” (biSOS R 1892). SCB provides the scanned publication on their website. Dollar Typing Service typed and delivered the data in 2015. All numerical variables but two have been checked. This is easy to do since nearly all columns should sum up to another column. For “Folkmangd” (population) the numbers have been corrected against U1892. The highest estimate of errors in the variables is 0.005 percent (0.5 promille), calculated at cell level. The two numerical variables which have not been checked is “hogsta_fyrk_jo“ and “hogsta_fyrk_ov“, as this cannot much be compared internally in the data. According to my calculations as the worst case scenario, I have measurement errors of 0.0043 percent (0.43 promille) in those variables.

---------------------------------------------
moricz_R1871_source_data.csv
---------------------------------------------
A UTF-8 encoded .csv-file with the source data. The variables are described in the adherent codebook moricz_R1871_source_data_codebook.csv.

Contains table 1 from “Bidrag till Sverige official statistik R) Valstatistik. II. Statistiska Centralbyråns underdåniga berättelse rörande kommunala rösträtten år 1871” (biSOS R 1871). SCB provides the scanned publication on their website. Dollar Typing Service typed and delivered the data in 2015. The variables have been checked for accuracy, which is feasible since columns and rows should sum. The variables that most likely carry mistakes are “hogsta_fyrk_al” and “hogsta_fyrk_jo”.

Datan består av ojämlikhetsmått på kommunal nivå för 1871 och 1892 som presenteras i doktorsavhandlingen "Institutions, Inequality and Societal Transformations" av Sara Moricz. Datan består också av råmaterialet
1) tabel 1 från “Bidrag till Sverige official statistik R) Valstatistik. XI. Statistiska Centralbyråns underdåniga berättelse rörande kommunala rösträtten år 1892” (biSOS R 1892)
2) tabel 1 från “Bidrag till Sverige official statistik R) Valstatistik. II. Statistiska Centralbyråns underdåniga berättelse rörande kommunala rösträtten år 1871” (biSOS R 1871)
Ojämlikhetsmått baserade på valdata 1871 och 1892 för svenska kommuner
Keywords: NATIONAL ECONOMY; NATIONALEKONOMI; ECONOMIC HISTORY; EKONOMISK HISTORIA; Economics; Nationalekonomi; Economic History; Ekonomisk historia